Search for solar atmospheric neutrinos with the ANTARES neutrino telescope. Issue 6 (1st June 2022) - ,; Albert, A.; Alves, S.; André, M.; Anghinolfi, M.; Anton, G.; Ardid, M.; Ardid, S.; Aubert, J.-J.; Aublin, J.; Baret, B.; Basa, S.; et al.
Abstract: Solar Atmospheric Neutrinos (SA ν s) are produced by the interaction of cosmic rays with the solar medium. The detection of SA ν s would provide useful information on the composition of primary cosmic rays as well as the solar density. These neutrinos represent an irreducible source of background for indirect searches for dark matter towards the Sun and the measurement of their flux would allow for a better assessment of the uncertainties related to these searches. In this paper we report on the analysis performed, based on an unbinned likelihood maximisation, to search for SA ν s with the ANTARES neutrino telescope. After analysing the data collected over 11 years, no evidence for a solar atmospheric neutrino signal has been found. An upper limit at 90% confidence level on the flux of solar atmospheric neutrinos has been obtained, equal to 7×10 -11 [ TeV -1 cm -2 s -1 ] at E ν = 1 TeV for the reference cosmic ray model assumed.